2023
DOI: 10.3389/fimmu.2023.1064839
|View full text |Cite
|
Sign up to set email alerts
|

A deep look into the storm: Israeli multi-center experience of coronavirus disease 2019 (COVID-19) in patients with autoimmune inflammatory rheumatic diseases before and after vaccinations

Abstract: ObjectiveWe aimed to characterize the course of COVID-19 in autoimmune inflammatory rheumatic disease (AIIRD) patients in Israel, taking into consideration several remarkable aspects, including the outcomes of the different outbreaks, the effect of vaccination campaigns, and AIIRD activity post-recovery.MethodsWe established a national registry of AIIRD patients diagnosed with COVID-19, including demographic data, AIIRD diagnosis, duration and systemic involvement, comorbidities, date of COVID-19 diagnosis, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The type of AIRD, disease activity, and organ involvements are also important while analyzing the impact of AIRDs on the COVID‐19 course 1,2 . In addition, classical comorbidities such as hypertension, obesity, and diabetes mellitus are generally more frequent among AIRD patients than the general population, and these comorbidities are associated with worse COVID‐19 outcomes 3,4 . On the other hand, most AIRD patients are on chronic immunosuppressive therapies, which may limit the hyperinflammation before the cytokine storm commences.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…The type of AIRD, disease activity, and organ involvements are also important while analyzing the impact of AIRDs on the COVID‐19 course 1,2 . In addition, classical comorbidities such as hypertension, obesity, and diabetes mellitus are generally more frequent among AIRD patients than the general population, and these comorbidities are associated with worse COVID‐19 outcomes 3,4 . On the other hand, most AIRD patients are on chronic immunosuppressive therapies, which may limit the hyperinflammation before the cytokine storm commences.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%
“…Regarding the treatment of AIRDs, glucocorticoids at a dose of ≥10 mg/d (prednisone equivalent), csDMARDs such as sulfasalazine, immunosuppressant drugs such as mycophenolate mofetil and tacrolimus, B cell depleting therapies such as rituximab and belimumab, and Janus kinase (JAK) inhibitors were the main drugs associated with worse COVID‐19 outcomes 3,4,6,26 . On the other hand, several studies suggested that anti‐tumor necrosis factor use was associated with a less severe COVID‐19 outcome 5,26–29 .…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Given established and potential COVID-19 risk factors, individuals with IMIDs are of particular interest and complexity for risk analysis. 2,3,4,5 This population has a higher rate of severe COVID-19 outcomes, but we need to understand why. Potential reasons include immune dysregulation, the use of immunomodulatory drugs (IMMs), and/or associated chronic comorbidities.…”
Section: Introductionmentioning
confidence: 99%